Discovering the basic social process of empowerment in health among families in relocation communities - Sumile, Earl Francis R.
Health is a multidimensional phenomenon influenced by factors in and out of the human body. The science of nursing, following the works of Florence Nightingale advocates for a milieu conducive to health. Working with communities and population groups, nurses strive to contribute to the goals of health promotion and disease prevention. The Alma Ata declaration of Primary Health Care (1978) speaks of an approach to peoples’ health by helping communities take responsibility for their health through their full participation and in the spirit of self-reliance and self-determination. The province of Bulacan, due to its proximity to Metro Manila has been the cradle of relocation sites for poor families affected by either calamities or urban development in cities. These relocation communities offer a unique scenario of poor access to healthcare that contributes to powerlessness . Thus, the need to understand how families in relocation communities take control of their healthcare needs remain a paramount concern. Their journey of empowerment on health is fittingly shared through their own words and explicated as a social process, and such in the objective of this qualitative research.